Assessing Exercise Habits of Cardiovascular Risks in Middle-Aged Adults: A Descriptive Study - S KalaBarathi; D Akshaya; M Kavitha; J Jagadeeswari (Wolters Kluwer Medknow Publications, 2024)
Background: Cardiovascular problems are the leading cause of death among adults in our country. These illnesses primarily affect metropolitan populations, particularly in major cities. To prevent these diseases, efforts have focused on identifying and controlling cardiovascular risk factors such sedentary lifestyle. Aim: The study aimed to assess the exercise habits of cardiovascular risks middle-aged adults. Materials and Methods: The research approach used in this study was quantitative approach with descriptive design. Purposive sampling technique was used to select the samples. Totally 60 cardiovascular patients were recruited from Saveetha Medical College and Hospital Thandalam, Chennai. Data were gathered by using structured questionnaires and risk score calculator. Collected data were analyzed by using descriptive and inferential statistics. Results: The above Table 1 shows that 59 (98.33%) had moderate level of physical activity and 1 (1.67%) had high level of physical activity among middle-aged adults. The mean and standard deviation of physical activity among middle-aged adults was 62.26 ± 5.92. The median was 62.0 with minimum score of 38.0 and maximum score of 73.0. The demographic variable age (χ 2 = 6.610, P = 0.037) had statistically significant association with level of physical activity among middle-aged adults at P < 0.05 level and the other demographic variables had not shown statistically significant association with level of physical activity among middle-aged adults. Conclusion: Physical activity promotion and support should be a global priority because of the health benefits it provides for adults.